Microclimate of Ayer Hitam Forest, Selangor - Nuruddin, Ahmad Ainuddin; Awaluddin, Salleh (Universiti Putra Malaysia Press, 1999)
Forest microclimatology is the study of physical processes in the forest atmospheric boundary layer over time. An understanding of these biophysical principles is essential in the development of sustainable forest management system in which forest resources can be utilized for ecological protection, timber resources, recreation, water resources and aesthetic appreciation. The objective of this paper is to characterise the microclimate of Ayer Hitam Forest. The study was conducted at Compartment 6 of the Ayer Hitam Forest. Parameters such as soil temperature, light, humidity, wind velocity and air temperature were monitored hourly during the study period. Data on the same parameters (except light) were also obtained from the Universiti Putra Malaysia, meteorological station. The UPM meteorological station had higher mean hourly air temperature, recorded higher maximum and lower minimum compared to Ayer Hitam Forest. Mean relative humidity at Ayer Hitam was higher than at UPM meteorological station while daily range relative humidity was higher at UPM meteorological station compared to Ayer Hitam. Mean soil temperatures at all depths in Ayer Hitam Forest were lower compared to the UPM meteorological station. Result from the study shows that microclimate of Ayer Hitam is different from UPM meteorological station.